Modeling and simulation of optimized photonic crystal waveguide for slow-light enhancement. (April 2020) - Hocini, A; Maache, M; Khedrouche, D
Abstract: We present a novel type of slow-light photonic crystal waveguide prepared by changing only the position of the second rows of holes in the direction of light propagation of a line-defect photonic crystal waveguide. A nearly constant group index is achieved of 30, 31 and 32 over wavelength ranges of 10.4 nm, 13.5 nm and 14.5 nm, respectively. In addition, a large normalized-delay-bandwidth product ranging from 0.201 to 0.300 is obtained at the operation wavelength of 1550 nm.